Squalene Loaded Nanoparticles Effectively Protect Hepatic AML12 Cell Lines against Oxidative and Endoplasmic Reticulum Stress in a TXNDC5-Dependent Way - Seyed Hesamoddin Bidooki; Teresa Alejo; Javier Sánchez-Marco; Roberto Martínez-Beamonte; Roubi Abuobeid; Juan Carlos Burillo; Roberto Lasheras; Victor Sebastian; María J. Rodríguez-Yoldi; Manuel Arruebo; Jesús Osada (MDPI AG, 2022)
Virgin olive oil, the main source of fat in the Mediterranean diet, contains a substantial amount of squalene which possesses natural antioxidant properties. Due to its highly hydrophobic nature, its bioavailability is reduced. In order to increase its delivery and potentiate its actions, squalene has been loaded into PLGA nanoparticles (NPs). The characterization of the resulting nanoparticles was assessed by electron microscopy, dynamic light scattering, zeta potential and high-performance liquid chromatography. Reactive oxygen species (ROS) generation and cell viability assays were carried out in AML12 (alpha mouse liver cell line) and a TXNDC5-deficient AML12 cell line (KO), which was generated by CRISPR/cas9 technology. According to the results, squalene was successfully encapsulated in PLGA NPs, and had rapid and efficient cellular uptake at 30 µM squalene concentration. Squalene reduced ROS in AML12, whereas ROS levels increased in KO cells and improved cell viability in both when subjected to oxidative stress by significant induction of Gpx4. Squalene enhanced cell viability in ER-induced stress by decreasing Ern1 or Eif2ak3 expressions. In conclusion, TXNDC5 shows a crucial role in regulating ER-induced stress through different signaling pathways, and squalene protects mouse hepatocytes from oxidative and endoplasmic reticulum stresses by several molecular mechanisms depending on TXNDC5.